Stimulated Raman backscattering from a laser wakefield accelerator. (19th July 2018) - Hussein, A E; Ludwig, J; Behm, K; Horovitz, Y; Masson-Laborde, P-E; Chvykov, V; Maksimchuk, A; Matsuoka, T; McGuffey, C; Yanovsky, V; Rozmus, W; Krushelnick, K
Abstract: Experiments were performed using the HERCULES laser system at the University of Michigan to study backward stimulated Raman scattering (BSRS) from a laser wakefield accelerator driven with a 30 fs pulse. 'The spectrum of backscattered light was found to be significantly broadened and red-shifted in cases where electrons were accelerated. BSRS broadening (red-shifting) was found to increase with respect to both plasma density and accelerated electron charge for laser powers exceeding 100 TW. Two-dimensional Particle-in-Cell simulations reveal temporal dynamics for the BSRS emission, which ceases as the wakefield bubble is evacuated of plasma electrons because of relativistic self-focusing. The intensity and duration of the BSRS signal was found to vary with plasma density and laser intensity. Both experimental and simulation results indicate that backward SRS is associated with plasma electron density within the wakefield bubble. This measurement can serve as a diagnostic of bubble dynamics, and is correlated with trapped electron charge in this regime.